The Relationship between Challenges Faced by Logistics Industry in Johor and the Implementation of Sustainable Logistics Practices - Ong, Chia Seng; Wan Ahmad, Wan Nurul Karimah (Research in Management of Technology and Business, 2025)
Sustainable logistics is garnering increased attention within the logistics industry. With increasing environmental concerns and regulatory pressures, logistics companies nowadays are embracing green practices. However, there is a gap in understanding the specific challenges that logistics companies face when implementing these sustainable practices in Johor. Hence, this study focuses on identifying the relationship between the extent of challenges faced by the logistics industry in Johor and the implementation of sustainable logistics practices. A stratified sampling method was applied to divide the logistics companies in Johor into subgroups based on different logistics sector such as freight forwarding, maritime logistics, road freight, air freight and warehousing to ensure each logistics sector is adequately represented. By using the quantitative method, a survey was conducted among 153 logistics companies in Johor with a response rate of 66%. The data collected were analysed using descriptive and correlation analysis. The results indicated that challenges related to technology, government and policy, supplier and partner engagement, and organizational and management support have a significant relationship with sustainable logistics practices. Considering these outcomes, logistics companies should prioritize addressing challenges related to technology adoption, government policies, supplier and partner engagement, and organizational management support to enhance their operational efficiency, achieve compliance with environmental regulations, gain a competitive advantage, and foster a sustainable and resilient logistics ecosystem.